Synthesis, Growth, and Characterization of Structural, Optical, and Nonlinear Optical Properties of L-Proline Tartrate Added by Lanthanum Chloride Single Crystal - Dessale Alemu; Tizazu Abza; M. Esthaku Peter; Micheal Negash (Advances in Materials Science and Engineering)
L-proline tartrate (LPT), 1 and 2 mol% of lanthanum chloride- (LaCl3-) doped LPT single crystals have been synthesized and grown using a slow evaporation solution method at room temperature. The crystals have undergone different characterization studies to test their suitability for device fabrication. The single crystal X-ray diffraction studies have revealed that both 1 and 2 mol% of LaCl3-doped LPT single crystals have been crystalized monoclinic crystal structure and space group P21. The UV-Vis-NIR spectrum analysis has shown that pure, 1, and 2 mol% of LaCl3-doped LPT single crystals have good optical transparency in the entire visible and near IR region. The optical band gap energy for pure, 1 and 2 mol% of LaCl3-doped LPT single crystals to be 4.9, 5, and 5.1 eV, respectively. The energy dispersive X-ray analysis confirmed that LaCl3 has been incorporated into LPT crystal. The second harmonic generation (SHG) efficiency for 1 and 2 mol% of LaCl3-doped LPT single crystals has been tested and found to be 1.27 and 1.6 times greater than that of the reference KDP crystal, respectively.